THE CORRELATION BETWEEN MOTIVATION AND READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 3 TAMPAKSIRING IN ACADEMIC YEAR 2020/2021 - Ni Pande Putu Wirayanti; Anak Agung Putri Maharani; Dewa Gede Agung Gana Kumara (Academic Journal on English Studies (AJOES), 2021)
The present study which made use of an ex-post facto research with correlation design was intended to figure out the significant correlation between motivation and reading comprehension of the eighth-grade students of SMPN 3 Tampaksiring in academic year 2020/2021. The samples of the research consisted of 94 students which were chosen by cluster sampling. The data were collected through administering the research instruments which were in the form of structured questionnaire and short answer task. The obtained data were statistically analyzed by using Pearson product moment correlation and t-test. The results of the data analysis clearly revealed the alternative hypothesis was accepted. In other words, the research findings confirmed that there is significant correlation between motivation and reading comprehension of the eighth-grade students of SMPN 3Tampaksiring in academic year 2020/2021.